Oxford textbook of global public health - Detels, Roger; Gulliford, Martin; Abdool Karim, Q; Tan, Chorh Chuan (Oxford : Oxford University Press, 2015)
Includes bibliographical references and index.
This is the sixth edition of the successful and internationally recognised textbook on global public health and epidemiology. The work comprehensively covers the scope, methods, and practice of the discipline.
This is the sixth edition of the successful and internationally recognised textbook on global public health and epidemiology. The work comprehensively covers the scope, methods, and practice of the discipline.
This edition previously issued in print: 2015.
Keywords: Public Health; World Health